Primary care medication safety surveillance with integrated primary and secondary care electronic health records: a cross-sectional study - Akbarov, Artur; Kontopantelis, Evangelos; Sperrin, Matthew; Stocks, Susan J.; Williams, Richard; Rodgers, Sarah; Avery, Anthony; Buchan, Iain; Ashcroft, Darren M. (Springer, 2015)
Introduction: The extent of preventable medication-related hospital admissions and medication-related issues in primary care is significant enough to justify developing decision support systems for medication safety surveillance. The prerequisite for such systems is defining a relevant set of medication safety-related indicators and understanding the influence of both patient and general practice characteristics on medication prescribing and monitoring.